Designing Management Education Framework Using IWA-2 Approaches - Agus Sukoco (Bandar Lampung University (UBL), 2013)
The guide IWA 2:2007 is a value to ISO 9001 system. This guide was elaborated by the experts in the field of education. It emphasizes so important elements of education as: educative value, concentration on social values etc. This guide contains practical instruments of introduction and improving the quality system in the field of education. IWA-2 quality management system can also be regarded as one of the approach as towards achieving best practices in teaching and learning. IWA-2 system not only focuses on quality assurance, but on the design of a quality management system. This leads to the achievement of customers satisfaction through incorporating their requirements in the system and measuring whether or not their satisfaction is achieved continuously. Thus, adopting this system will ensure the teaching and learning processes are of creditable standards and quality. This paper thus, discusses how best practices in teaching and, in general, were designed and practiced using the IWA-2 quality management system framework.The educational organization conduct internal audits according to an audit program to assess the performance of the quality management system and educational process, verify the use established method for educational process. Standard ISO 19011:2011 provides guidance on auditing management systems, including the principles of auditing, managing an audit program and conducting management system audits, as well as guidance on the evaluation of competence of individuals involved in the audit process, including the person managing the audit program, auditors and audit teams.